(untitled) (Journal of Dhaka Medical College, 2020)
Background: Bacterial bloodstream infections (BSI) are a major problem for health care personnel’s, which leads to high morbidity and mortality of patients. Early and timely diagnosis and appropriate medication will be the best way to save the lives of affected ones. Aim: The aim of the present study was to determine the bacterial profile of bloodstream infections and their antibiotic susceptibility pattern. Methods: This descriptive cross-sectional study was carried out at the Microbiology Laboratory, Popular diagnostic Ltd, Dhanmondi, Dhaka over a three months periods, from November’ 2017 to January’ 2018. A total 822 blood culture samples were screened. The positive blood cultures were examined and the organisms were identified as per standard procedures. Antimicrobial susceptibility testing was performed for all isolates by using disk diffusion technique, according to CLSI guidelines 27. Results: From total blood culture samples, 105 (12.77%) were positive. The most common isolated pathogens were Salmonella Typhi, 59 (56.19.5%). Other isolates are Salmonella paratyphi A & B, 11(10.47%); Eschericia coli 14 (13.33%); Klebsiella spp, 05(04.76%); Acinetobacter spp.11 (10.47%) Enterococcus spp. 02 (01.90%); Staphylococcus aureus, 02 (01.90%) and one Candida spp (0.95%). S. Typhi showed 100% sensitivity against Ceftriaxone and Cefixime, and also more than 80% sensitive against first-line drugs (Chloramphenicol and Co-trimoxazole). Almost all the strains were found resistant towards Nalidixic acid (sensitivity 05.71%). Most of the Staphylococcus aureus and Enterococcus spp were susceptible to Vancomycin and Linezolid. More than 80% of E. coli and Klebsiella spp.are sensitive to Imipenem and Meropenem and least sensitivity show against Ciprofloxacin, Cephradine and Ceftriaxone. Conclusion: Ongoing surveillance for antimicrobial susceptibility remains essential, and will enhance efforts to identify resistance and attempt to limit its spread. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 114-122